Coaching and Development of Pencak Silat Sports Based on Living Respect Values in Positive Youth Development - Jeki Purnama Putra; Nurlan Kusmaidi; Mulyana; Amung Ma’mun (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This study aims to examine whether the integration of the concept of "living respect" in a pencak silat training program can enhance the development and understanding of living respect values within the framework of positive youth development. This study employs a group-based experimental design that includes 60 participants in a training program, with the participants being divided into two groups: a control group and an experimental group. The control group receives regular pencak silat training, while the experimental group undergoes pencak silat training that incorporates sub-dimensions of living respect, such as attitudes of tolerance, embracing differences, promoting equality, and opposing discrimination. The research results indicate that the experimental group experiences a significant improvement in the development of living respect skills compared to the control group. The integration of living respect values into the pencak silat training appears to offer effective benefits to the participants, particularly in terms of enhancing social and emotional skills that are vital in daily life. Therefore, the integration of living respect within sports and educational training can serve as an effective alternative for enhancing holistic living respect values.